Mcquail?s mass communication theory 6th ed. - McQuail, Denis (London SAGE Publications, 2010)
McQuail's Mass Communication Theory has been the benchmark for studying mass communication theory for more than 25 years. It remains the most authoritative and comprehensive introduction to the field and still offers unmatched coverage of the research literature.
Includes bibliographical references
Keywords: Mass media